Farmers’ Satisfaction of the Service Quality of Broiler Contract Farming Model in Banyumas Regency - Mochamad Sugiarto; Yusmi Nur Wakhidati; Hudri Aunurrohman (Buletin Peternakan, 2019)
This study aims at identifying nucleus companies’ service quality, broiler farmers’ satisfaction and the relationship between contract farming services quality and broiler farmers’ satisfaction in Banyumas Regency. The study takes survey method to broiler farmers participating in contract farming programs from five nucleus companies in Banyumas Regency as its population. 50 broiler farmers are selected using the proportional random sampling method based on Slovin formula as respondents. The data obtained are analyzed by employing descriptive statistics and Correlation Rank Spearman Analysis. The results show that the farmers are averagely 44 years old with mostly junior high education, and 76% of the respondents have broiler farming as their main livelihood. The farmers have quite a long time of experience (8.92 years) in raising broiler farming. Their satisfaction of the contract farming model’s service is of medium category (score 84.02) and their perception of the nucleus companies’ service quality is of medium category (score 86.34). The Spearman Rank Correlation analysis shows that the nucleus companies’ service quality is significantly related to the broiler farmers’ satisfaction (P<0.01) with a strong correlation coefficient of 0.761. The nucleus companies’ services in broiler contract farming model must be continuously improved to increase broiler farmers’ satisfaction.